IKLIM ORGANISASI DAN MOTIVASI BERPRESTASI TERHADAP KEPUASAN KERJA DAN KINERJA GURU - Liana, Yuyuk (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: Purpose of this study was to determine the effect of achievement motivation. Organizational climate and job satisfaction as well as the indirect effect of organizational climate, achievement motivation on the performance of employees throught job satisfaction. By purposive random sampling amounting 103 teacher. The result showed that all paths are significant. The path to the value of X1 to X3 0.042,the path to the value of X2 to X3 0.005, the path to the value of X1 to X4 0.045,  the path to the value of X2 to X4  0.000 and the path to the value of X3 to X4 0.022. With indirect influence that has the greatest values is the value is the influence of achievement motivation on employee performance throught employee satisfaction by 0.094 Keyword: Organizational Climate, Motivation, Satisfaction, Performance